‘Drop that blade or I’ll show you my pussy’ : the visual (non)representation of the vagina in campaigns against female genital mutilation - Viljoen, Frans (University of Pretoria, 2019)
Mini Dissertation (MPhil)--University of Pretoria, 2018.